Chlamydia trachomatis and Genital Mycoplasmas: Pathogens with an Impact on Human Reproductive Health. (30th December 2014) - Ljubin-Sternak, Sunčanica; Meštrović, Tomislav
Abstract : The most prevalent, curable sexually important diseases are those caused by Chlamydia trachomatis ( C. trachomatis ) and genital mycoplasmas. An important characteristic of these infections is their ability to cause long-term sequels in upper genital tract, thus potentially affecting the reproductive health in both sexes. Pelvic inflammatory disease (PID), tubal factor infertility (TFI), and ectopic pregnancy (EP) are well documented complications of C. trachomatis infection in women. The role of genital mycoplasmas in development of PID, TFI, and EP requires further evaluation, but growing evidence supports a significant role for these in the pathogenesis of chorioamnionitis, premature membrane rupture, and preterm labor in pregnant woman. Both C. trachomatis and genital mycoplasmas can affect the quality of sperm and possibly influence the fertility of men. For the purpose of this paper, basic, epidemiologic, clinical, therapeutic, and public health issue of these infections were reviewed and discussed, focusing on their impact on human reproductive health.